The Issues of Decisionism in the Implementation of the Constitutional Authority - Eduard Galitsky, Nikolay Antsiferov, (Opción, 1970)
The article deals with the problematic of constitutional decision-making, decisionism and constitutional duty in the constitutional law system via comparative qualitative research methods. As a result, the methodology for determining relevant legal decisions that are objectively related to the object of constitutional-legal relations is the issue of constitutional-legal decisionism. Summing up the analysis of the perspectives of the problems of constitutional legal decisionism, it can be said that it contains questions related to the development of a constitutional legal decision.